MANAL ALDOWAYAN: IMMORTAL TRACES. - LENTCHNER, ANNA (ArtAsiaPacific)
An interview with Saudi Arabian artist Manal AlDowayan, is presented who discusses her journey from a computer programmer to a distinguished artist in Saudi Arabia, focusing on her exploration of collective memory through participatory installations like Oasis of Stories. Topics include her inspiration from Saudi heritage, politics of archiving, and the significance of community engagement.